De-constructing Asian diaspora : reclaiming or reshaping identity and culture? - Ong, Eileen Ah Buan. (2010)
Because Asian Diasporic predicaments are the hardest to define. No words in the English Dictionary aptly describe their straddled positions. After dissecting the texts, protagonists continue to feel the tension between two distinct cultures of opposing values and belief. As protagonists still feel a sense of affiliation to their native land, they continue to rely on their cultural patrimony in their decision-making. However, their reliance is problematic due to the nature of memory and perception. The three selected texts negotiate this tension in ways that are similar and different. Protagonist Etsuko after going through so much change finally settled in London leaving the old house where Keiko had once lived. She feels very much alone for she has clear difficulty passing on her roots to Niki whose idea of marriage and children went the opposite ways of hers. However, she continues to hold on to her patrimonial culture to live. She feels aloneness for no westerners can understand her and therefore finds comfort in the nature that surrounds her. Ishiguro does not offer a good way forward to this persona. Sunny on the other hand in The Match seems to have gone to a stage where an epiphany is established, and that being the acceptance of irreclaimable nature of the past. Although author seems to offer a possible way out through art, this seems to be preposterous in the end. Reconciliation with his wife and a returned interest to his child does offer a way forward but not yet successful. As with Syal’s Life isn’t all ha ha hee hee, all protagonists have failed but one which is Tania. Instead of taking a stance that swings too much to the left or right, she is the only one able to maintain a balance between the two cultures. However, a clear understanding that Asian Diaspora has belong to nowhere in particular but are just flexible enough to constantly adjust to a mid point to make sense of her world. Although memory and perception continue to be unreliable and warped, ability to maintain this equilibrium of the two cultures suggest a way forward. This is an act to reshape and not reclaim Tania’s identity as it changes with the norms of both cultural patrimony as well as host culture.